Helicobacter pylori infection as a protective factor against multiple sclerosis risk in females. Issue 6 (19th January 2015) - Pedrini, Marzena J Fabis; Seewann, Alexandra; Bennett, Kirsten A; Wood, Alex J T; James, Ian; Burton, Jason; Marshall, Barry J; Carroll, William M; Kermode, Allan G
Abstract : Background: In recent years, a relationship between Helicobacter pylori and many disease conditions has been reported, however, studies in its relationship with multiple sclerosis (MS) have had contradictory results. Objective: To determine the association between the H. pylori infection and MS. Methods: 550 patients with MS were included in the study and were matched by gender and year of birth to 299 controls. Patients were assessed for clinical and demographic parameters. An enzyme immunoassay was used to detect the presence of specific IgG antibodies against H. pylori in the serum sample of both groups. Results: H. pylori seropositivity was found to be lower in the patients with MS than in controls (16% vs 21%) with the decrease pertaining to females (14% vs 22%, p=0.027) but not males (19% vs 20%, p=1.0). When adjusted for age at onset, year of birth and disease duration, H. pylori seropositive females presented with a lower disability score than seronegative females (p=0.049), while among males the reverse was true (p=0.025). There was no significant association between H. pylori seropositivity and relapse rate. Conclusions: Our results could reflect a protective role of H. pylori in the disease development. However, it may be that H. pylori infection is a surrogate marker for the 'hygiene hypothesis', a theory which postulates that early life infections are essential to prime the immune system and thus prevent allergic and autoimmune conditions later in life. The fact that the association between H. pylori seropositivity and MS risk was seen almost exclusively in females requires further investigation.